2017
DOI: 10.1115/1.4037668
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Study of NiCrAlY and FeCrAlY Exposed to Superheated Steam at 800 °C

Abstract: Supercritical water-cooled reactor (SCWR) was chosen as Generation IV reactor concept in Canada to utilize Canada's expertise and technical capabilities from past research and designs. The conceptual design of Canadian SCWR has a core outlet temperature of 650 °C at 25 MPa and a peak cladding temperature as high as 800 °C. Corrosion/oxidation resistance is an important factor in material selections and also coating considerations. Most of the reported supercritical water (SCW) test data have been obtained at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Considerable efforts have been dedicated to the development of coatings for super-critical power plants [12][13][14][15][16][17][18][19] but little work has been published regarding the behaviour and coatings under high pressure steam. Coatings such as MCrAlY overlays (M = Ni, Fe) [20,21] ceramics such as Al 2 O 3 [22], and diffusion aluminides deposited by slurry application [23][24][25] or by pack cementation [26] have been studied over the past few years and in most cases these coatings displayed a substantial improvement in terms of high pressure steam oxidation resistance. For instance, specimens of P92, both uncoated and coated with a slurry aluminide were exposed to real operating conditions in a bypass of a steam power plant and the results were compared to those obtained in the laboratory under atmospheric steam [23].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable efforts have been dedicated to the development of coatings for super-critical power plants [12][13][14][15][16][17][18][19] but little work has been published regarding the behaviour and coatings under high pressure steam. Coatings such as MCrAlY overlays (M = Ni, Fe) [20,21] ceramics such as Al 2 O 3 [22], and diffusion aluminides deposited by slurry application [23][24][25] or by pack cementation [26] have been studied over the past few years and in most cases these coatings displayed a substantial improvement in terms of high pressure steam oxidation resistance. For instance, specimens of P92, both uncoated and coated with a slurry aluminide were exposed to real operating conditions in a bypass of a steam power plant and the results were compared to those obtained in the laboratory under atmospheric steam [23].…”
Section: Introductionmentioning
confidence: 99%
“…Bsat et al [2018-1] tested NiCrAlY coated Alloy 214 specimen coupons in SCW (700 o C, 25 MPa, 150 ppb O2, pH 7, 7 mL/min) for 1,000 hours and found a thin oxide scale likely containing Cr2O3 and Ni(Al,Cr)2O4. Saez-Maderuelo et al [2018] when testing NiCrAl coupons in SHS (800 o C, 0.1 MPa) noted that an oxide scale formed containing a mixture of NiO,(Cr,Al)2O3 spinel, chromia, and alumina after 300 hours, and alumina and chromia after 600 hours. In general, both in this study and in previous work, the oxide scales observed were thin and without distinct phase separation, no matter the test condition in SHS and SCW.…”
Section: Cs Specimensmentioning
confidence: 99%